Efeito do tratamento com 17β-estradiol na sinalização de cálcio e na geração de ERO no hipocampo de ratas senescentes - Machado, Sabrina Nunes [UNIFESP] (2010)
In Brazil, the elderly population is growing exponentially. At 1960, the number of elderly with 60 years was approximately 3 million people. According to projections made by Brazilian Institute of Geography and Statistics (IBGE), the in 2025 the number of elderly will be more than 30 million and the Brazil will be the sixth country with largest number of elderly. In old-age, neurodegenerative diseases are highly prevalent. Evidence indicates that many degenerative processes of aging are associated with alterations in calcium homeostasis, with imbalance between reactive oxygen species (ROS) production and an antioxidant defenses that may lead to the mitochondrial dysfunction and apoptosis. The estrogen therapy with 17â-estradiol has been shown present antiapoptotic and antioxidant effects. Thus, the purpose of our study was to investigate the effect of treatment with 17â-estradiol in calcium signaling and on the generation of ROS in senescent rats. The analysis of senescent animals showed a dysfunction in intracellular buffering system, a tendency toward greater production of ROS and a reduction of the mitochondrial metabolic activity. Our results showed that estrogen therapy lead to an increase of capacity of intracellular calcium stores, an increased response to acetylcholine stimulation, a decreased production tendency of ROS and an increased mitochondrial metabolic activity. These findings indicate that estrogen therapy exhibit antioxidant properties and calcium signaling modulator in senescence.